2021
DOI: 10.1038/s41375-021-01165-w
|View full text |Cite
|
Sign up to set email alerts
|

The association between deaths from infection and mutations of the BRAF, FBXW7, NRAS and XPO1 genes: a report from the LRF CLL4 trial

Abstract: Causes of death, in particular deaths due to infection, have not been widely studied in randomised trials in chronic lymphocytic leukaemia. With long-term follow-up (median 13 years) we examined the cause of death in 600/777 patients in the LRF CLL4 trial. Blood samples, taken at randomisation from 499 patients, were available for identifying gene mutations. Infection was a cause of death in 258 patients (43%). Patients dying of infection were more likely than those who died of other causes to have received ≥2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…This implies that individuals carrying a loss of function mutations in SCF complex genes could be highly susceptible to bacterial infections. Indeed, a recent cohort-based study indicated that almost 43% of the CLL (Chronic Lymphocytic Leukaemia) patients, caused by mutations in the FBXW7 gene, succumb to bacterial pneumonia and sepsis followed by fungal infections (25). Our findings therefore provide an unexpected molecular explanation of the enhanced risk of infections of the CLL patients, especially to respiratory pathogens.…”
Section: Main Textmentioning
confidence: 57%
“…This implies that individuals carrying a loss of function mutations in SCF complex genes could be highly susceptible to bacterial infections. Indeed, a recent cohort-based study indicated that almost 43% of the CLL (Chronic Lymphocytic Leukaemia) patients, caused by mutations in the FBXW7 gene, succumb to bacterial pneumonia and sepsis followed by fungal infections (25). Our findings therefore provide an unexpected molecular explanation of the enhanced risk of infections of the CLL patients, especially to respiratory pathogens.…”
Section: Main Textmentioning
confidence: 57%
“…Heterozygous mutations in FBXW7, particularly R505C (a critical residue in substrate recognition pocket) variant, trigger multiple carcinomas and lymphocytic leukemia in humans ( 49 , 50 ). A recent cohort-based study indicated that almost 43% of the patients with chronic lymphocytic leukemia (CLL) succumb to bacterial pneumonia and sepsis, followed by fungal infections ( 51 ). This corroborates with our observation of the abrogated ability of host cells bearing FBXW7 mutation to sense and eliminate pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…FBXW7 (also known as CDC4) is a component of the S-phase kinase-associated protein 1 (SKP1)/CUL1/F-box (SCF) E3 ubiquitin ligase complex, which functions as a tumor suppressor which is frequently altered in cancer [ 187 , 188 ]. It has been reported that loss of FBXW7 in the presence of the BRAF V600E mutation is consequential and sufficient to drive tumorigenesis in mouse models [ 189 ].…”
Section: Regulation Of Targeted Therapy Through Modulating Protein De...mentioning
confidence: 99%